Hepatic Haemangioma Masquerading as the Gallbladder in a Case of Gallbladder Agenesis: A Case Report and Literature Review. (5th July 2010) - Stephenson, James A.; Norwood, Michael; Al-Leswas, Dhya; Al-Taan, Omer; Beable, Richard; Lloyd, David M.; Dennison, Ashley R.
Abstract : Gallbladder agenesis is uncommon. In contrast, liver haemangiomas are the most common type of benign liver lesions. We describe the first documented case of gallbladder agenesis where the clinical presentation was consistent with biliary colic, and radiological investigation suggested the presence of gallstones. Subsequent operative findings revealed a solitary haemangioma of the liver sited in the normal position of the gallbladder fossa but with absence of the gallbladder. It is important that clinicians should keep gallbladder agenesis in mind when the gallbladder appears abnormal on preoperative imaging studies and cannot be found at laparoscopy. As symptoms will improve in 98% of cases, it is very important to avoid unnecessary intervention in patients who have a negative laparoscopy. The clinical presentation, investigations, and operative findings are discussed with a review of other relevant reported cases in the literature.